The influence of antineoplastic agents on the peri-implant bone around osseointegrated titanium implants: an in vivo histomorphometric and immunohistochemical study - Matheus, Henrique Rinaldi [UNESP]; Ervolino, Edilson [UNESP]; Gusman, David Jonathan Rodrigues [UNESP]; Forin, Luiz Guilherme [UNESP]; Piovezan, Bianca Rafaeli [UNESP]; de Almeida, Juliano Milanezi [UNESP] (Springer Nature, 2022)
Background and objective: The interaction between antineoplastic drugs used for treating cancer and non-affected tissues remains poorly assessed and may be critical for maintaining the quality of life for patients during and after treatment. This pre-clinical study evaluated the effects of cisplatin (CIS) and 5-fluorouracil (5-FU) on the peri-implant repair process around osseointegrated titanium implants installed in the tibiae of rats. Material and methods: Were used 90 male rats, randomly divided into three groups (n = 30): physiological saline solution (PSS), CIS, and 5-FU. Titanium implants (4.0 × 2.2 mm) were inserted in both tibiae of all animals at day 0. The animals received either PSS, CIS, or 5-FU at 35 and 37 days. Euthanasia was performed at 50, 65, and 95 days after surgery. Histometric (bone/implant contact [BIC]) and bone area fraction occupancy (% BAFO), histological, and immunohistochemical (for bone morphogenetic protein 2/4 [BMP2/4], Runt-related transcription factor 2 [RUNX2], osteocalcin [OCN], and tartrate-resistant acid phosphatase [TRAP]) analyses were performed. Data were statistically analyzed. Results: Groups CIS and 5-FU presented lower BIC and lower BAFO as compared with PSS in all time points. The imbalance in bone turnover was observed by the lower number of BMP2/4-, RUNX2-, and OCN-positive cells/mm2 and the higher number of TRAP-positive cells/mm in groups CIS and 5-FU as compared with PSS in all time points. Persistent and exacerbated inflammation was observed in groups CIS and 5-FU. Conclusions: Both antineoplastic agents interfered negatively in the bone turnover around osseointegrated titanium implants. Clinical relevance: Closer and more careful follow-up of patients with osseointegrated implants that will undergo chemotherapy with either CIS or 5-FU shall be performed.
Keywords: Antineoplastic agents; Bone implant interface; Cisplatin; Fluorouracil; Osseointegration